Suma y resta de matrices - Gutiérrez-Montenegro, Marco (My University, 2017)
Explica las operaciones de suma y resta de matrices así como las condiciones que se deben cumplir para realizar estas dos operaciones entre matrices.

It explains the operations of addition and subtraction of matrices as well as the conditions that must be met to perform these two operations between matrices.
Keywords: Operaciones; Sumas; Restas; Matrices